Range and Quality of Information about Financial Instruments in Financial Statements of Companies Listed on the Warsaw Stock Exchange - Rówińska, Małgorzata (Studia Oeconomica Posnaniensia, 2016)
The objective of the paper is to analyse the range of reporting information about financial instrument presents for companies listed on the Warsaw Stock Exchange. The analysis concerned the following problems: classifications of financial instruments, balance sheet valuation, financial risk connected with financial instruments, and hedge accounting.